2018
DOI: 10.1002/esp.4385
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity assessment in Mediterranean vineyards using improved stock unearthing method, LiDAR and soil erosion field surveys

Abstract: The interaction between processes and landforms is accelerated in vineyards due to bare tilled soils that enhance splash, runoff, and erosion. Traditionally, in order to assess these processes, the stock unearthing method (SUM) is considered a useful methodology that uses the graft union of the vine plant as passive bio-indicator of the topsoil level changes. However, SUM assumes that the topography between the rows is planar when development of a model of the current micro-topography is performed. Thus, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 66 publications
(77 reference statements)
2
26
0
2
Order By: Relevance
“…Planning infrastructures to manage flood risk is related to connectivity (Parson et al 2015), circularity (Kirchherr et al 2017;Comino et al 2018;Keesstra et al 2018) and finding a balance between natural and urban elements (Gaines 2016). Moreover, in a fast developing city, the loss of circularity is often associated with the altered hydrological cycle, implying that water is not a natural, valuable resource, but rather a threat to the urban environment, when it flows at rates different from those of natural paths, from/toward locations that are functional to the development of human activity rather than to the environmental dynamics, through man-managed (often fast) connections, with quality standards far from those provided by natural water bodies (EPA 2005).…”
Section: Flood Protection and Risk Managementmentioning
confidence: 99%
“…Planning infrastructures to manage flood risk is related to connectivity (Parson et al 2015), circularity (Kirchherr et al 2017;Comino et al 2018;Keesstra et al 2018) and finding a balance between natural and urban elements (Gaines 2016). Moreover, in a fast developing city, the loss of circularity is often associated with the altered hydrological cycle, implying that water is not a natural, valuable resource, but rather a threat to the urban environment, when it flows at rates different from those of natural paths, from/toward locations that are functional to the development of human activity rather than to the environmental dynamics, through man-managed (often fast) connections, with quality standards far from those provided by natural water bodies (EPA 2005).…”
Section: Flood Protection and Risk Managementmentioning
confidence: 99%
“…Rainfall erosivity is the potential possibility of soil erosion induced by rainfall, which is the most important external driving force and the dynamic indicator of soil separation and transportation [45,46]. Many of the existing classic and straightforward algorithms for estimating this factor are mainly based on annual rainfall, monthly, daily, or hourly rainfall [47][48][49].…”
Section: Rainfall-runoff Erosivity Factor (R)mentioning
confidence: 99%
“…In addition, there is a doubt about how this strategy affects the final result. It is accepted and demonstrated that soil erosion is different at different locations and slope positions such as what Rodrigo-Comino et al [32] found. However, how different the erosion rate will be in the same hillslope position and soil type from one inter-row to the nearest one is still unclear.…”
Section: Introductionmentioning
confidence: 74%